PENGARUH PERSONAL SELLING TERHADAP VOLUME PENJUALAN MOBIL, TOYOTA PADA PT. HADJI KALLA CABANG URIP SUMOHARJO DI KOTA MAKASSAR - Nurlina Nurlina (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to determine the effect of the cost of personal selling to sales volume of Toyota cars at PT. Hadji Kalla Branch Urip Sumoharjo in Makassar with the method used is a simple regression analysis method that this method be used as a measuring tool in the statistical results of the discussion, and analyzed so as to provide complete information to the problems faced. Quantitative methods that determine the influence of personal selling variable costs to sales volume of Toyota cars at PT. Hadji Kalla Makassar Branch Urip Sumoharjo. The results showed that the cost of personal selling are having a significant effect on the sales volume, therefore, the company should increase the budget cost of personal selling to increase sales volume. Then the influence of personal selling variable costs to sales volume of Toyota cars at PT. Hadji Kalla Makassar Branch Urip Sumoharjo is at 59.8% while the remaining 40.2% (100 to 59.8%). Caused by other factors including advertisement, publicity, sales promotion and other marketing mix factors, namely price, place, and product.